Santripreneurship development for motor skill optimization through handicrafts at tpq hidayatul mubtadiin, temanggung - Eko Sariyekti; Muhammad Ifandi; Yusril Anwar; Setyo Wicaksono; Afidah; Muh. Hasbi Khilal Zuhri (Yayasan Azhar Amanaa Yogyakarta, 2025)
This service offers a new approach in the development of early childhood entrepreneurship in rural areas through the utilization of fine motor skills to produce feathered keychain handicrafts. The program aims to build entrepreneurial awareness from an early age through a combination of education, creativity, and economic independence. In Ploso Hamlet, Temanggung, many children have free time that has not been utilized productively. This program will introduce the basic techniques of making woven keychains and basic entrepreneurship training. Based on a survey, 75% of children in this hamlet do not have additional activities after school, and only 15% of families have micro businesses. This program is expected to optimize local potential, improve children's skills, and encourage entrepreneurial spirit. Through this activity, it is expected that children in Ploso Hamlet can utilize leisure time productively, develop new skills, and contribute to the economic independence of their families.